Dysregulated autophagy at the nexus of type 2 diabetes mellitus and pancreatic cancer pathogenesis - Li, Longmei; Chen, Yatong; Wang, Shushu; Du, Wanying; Lao, Tianfeng; Chen, Feng; Yao, Gengzhen; Chen, Wensheng; Li, Xuewen; Liu, Chunping; Xue, Xiaoguang (Frontiers in Endocrinology, 2026)
Diabetes Mellitus (DM) and Pancreatic Cancer (PC) are two major diseases that pose severe threats to global health, and their comorbidities have drawn increasing attention in recent years. Substantial epidemiological evidence indicates that type 2 diabetes mellitus (T2DM) is not only a risk factor for PC development but also an early clinical manifestation. The pathogenesis of these two conditions is interactive, wherein autophagy—a highly conserved intracellular catabolic process—plays a central role in maintaining pancreatic β-cell function, regulating insulin sensitivity, and determining the fate of PC cells. In diabetes, dysregulated autophagy contributes to β-cell failure and insulin resistance; in PC, autophagy plays a dual role, potentially suppressing tumorigenesis in early stages while supporting cancer cell survival and proliferation during progression, thereby mediating chemotherapy resistance. We review the epidemiological links, shared risk factors, and mutual influences of clinical management strategies in the comorbidity of diabetes and PC and focus on dissecting the pivotal role of autophagy at the intersection of their mechanisms. To elucidate the connection of autophagy pathways in both diseases, we aimed to provide novel perspectives on their common pathophysiological basis and identify potential targets for innovative therapeutic strategies against this comorbidity.